Letter - Garbutt, G.
001-0192-001 11.4.37 40 Briardene Avenue Scarboro' Yorks. Dear Sir May I be permitted to ask if you think there will be vacancies for skilled tradesmen in Spain when peace is restored, which I sincerely hope is not far off. I admire the pluck shown by the Gov forces and have a desire to live and work among these people. Perhaps you could advise me in your reply. I am a cable jointer, been in my present job since leaving H.M. Forces, 16 years ago. Obliged Yours sincerely G. Garbutt 292/946/1/192